Effects of dietary diversification during pregnancy on birth outcomes in east Gojjam, northwest Ethiopia: A prospective cohort study - Wondemagegn, Amsalu Taye; Tsehay, Binalfew; Mebiratie, Akiloge Lake; Negesse, Ayenew (Frontiers in Public Health, 2022)
Introduction Adequate nutrient intake during pregnancy is an important key factor affecting fetal growth and birth outcomes, as well as maternal health, as demonstrated by experimental animal studies. However, the few human studies available, especially those conducted in the least developed countries (LDCs), are much less consistent. Therefore, this study aimed to investigate the association between dietary diversification during pregnancy and birth outcomes in Gojjam, Ethiopia. Methodology A facility-based prospective cohort study was conducted on 416 pregnant mothers (exposed and non-exposed) from December 2019 to January 2020. Information about the Women's Dietary Diversity Score (WDDS) was collected using the Food and Agricultural Organization's guidelines. Data were collected through interviewer-administered questionnaires and measurements. Log-binomial regression analysis was performed to estimate the relative risk of adverse birth outcomes. Energy, macronutrient, and micronutrient amounts were calculated using the nutrition survey software version 2007. The differences between groups were noticed using analysis of variance. Eta squared was estimated in the current study. Results The overall magnitude of low birth weight, preterm birth, and stillbirth in the study area, respectively, was 41%, 38%, and 4%. After adjustment for baseline characteristics, this study revealed that pregnant women in the inadequate WDDS group were at increased risk of LBW (ARR = 6.4; 95% CI: 3.4, 12) and PTD (ARR = 6.3; 95% CI: 3.3, 11.95) as compared with their counterparts but no difference in the occurrence of stillbirth (ARR = 1.08; 95% CI: 0.20, 5.79). Conclusion Overall, this study found a large magnitude of low birth weight and preterm birth. Inadequate intake of dietary diversity during pregnancy significantly increased the rate of low birth weight and preterm birth. Thus, we recommend the concerned body to work on improving the feeding practices of pregnant mothers in the study area.